PLAGIAT SEBAGAI BENTUK PELANGGARAN AKADEMIK DALAM PARADIGMA TEORI PROPERTY - Ariya Zurnetti dan Roni Efendi (Fakultas Hukum Universitas Tamansiswa Padang, 2018)
making scientific papers in the academic world is a testament to the competence of an academic. Writing scientific papers, not infrequently an action occurs in which the ideas set forth in scientific work are not the results of research that has been carried out. So that quoting other people's writings or ideas becomes one of the shortcuts to laying out ideas, concepts and analysis in scientific papers. This is where a problem often occurs when a quote taken from a particular work does not provide an explanation of the origin of the idea. This is then known as the act of plagiarism. In the perspective of the theory of private property, scientific work is the absolute right of the person who created it. Then every scientific work must be protected for violating scientific work. In addition to the theory of private property, the labor theory of property confirms the absolute rights possessed by the creator of the scientific work produced and provides legal certainty for the protection of these rights, both theories are the spirit of the birth of copyright law in Indonesia.